2016
DOI: 10.1016/j.eml.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic perspective on in situ nanomechanics

Abstract: Nanostructured materials exhibit superior physical and mechanical properties, and they hold great promise for enabling the development of novel micro/nano electromechanical systems. A fundamental understanding of the mechanical deformation and degradation in nanostructured materials is critical for designing the damage-tolerant nanostructures and devices. The in situ transmission electron microscopy provides a novel approach to uncover the dynamic deformation mechanisms in nanostructured materials, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 152 publications
(264 reference statements)
0
15
0
Order By: Relevance
“…Similar to the method to create thin NWs in the AFM force spectroscopy, thin metal NWs were formed with stable contacts between a metal rod and a scanning tunneling microscope (STM) probe inside TEM, especially under applied voltage [107,108]. Stable contacts can also form between thin metal NWs inside TEM by cold welding [109].…”
Section: Tensionmentioning
confidence: 99%
“…Similar to the method to create thin NWs in the AFM force spectroscopy, thin metal NWs were formed with stable contacts between a metal rod and a scanning tunneling microscope (STM) probe inside TEM, especially under applied voltage [107,108]. Stable contacts can also form between thin metal NWs inside TEM by cold welding [109].…”
Section: Tensionmentioning
confidence: 99%
“…Some experimental insights into the GB migration have been obtained in the past two decades, with the spring up of well-designed in situ transmission electron microscopy (TEM) techniques 10,20,21 . For example, in situ heating experiments have revealed a thermal-induced GB migration in Au and Al thin films at 0.4–0.7 T m ( T m is the melting temperature) through the atomic shuffling 22 or GB disconnection 23 mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies have shown that the important mechanisms of plastic deformation in FCC nanowires are slip through perfect and partial dislocations and deformation twinning. The competition between slip and twinning mechanisms depends mainly on the crystallographic orientation, size, shape and loading mode (tension/compression), temperature and strain rate [13,14,15]. However, among all these factors, crystallographic orientation has the strongest influence followed by mode of loading [12,13].…”
Section: Introductionmentioning
confidence: 99%